Growth patterns of white British and Pakistani children in the Born in Bradford cohort: a latent growth modelling approach. Issue 4 (9th December 2014) - Mebrahtu, Teumzghi F; Feltbower, Richard G; Petherick, Emily S; Parslow, Roger C
Abstract : Background: Childhood growth patterns have been proposed as a key predictor of health during childhood and adult life. In earlier studies, however, the statistical methodologies employed failed to uncover the more subtle patterns in growth trajectories. Methods: Study participants were 1364 singleton term children (602 white British and 762 Pakistani origin) drawn from the Born in Bradford (BiB) prospective cohort. Weights were measured at 0, 1, 3, 6, 12, 18, 24 and 36 months. Age-specific and sex-specific standardised weight scores were derived based on the World Health Organisation growth standards. Missing growth data were estimated using Full Information Maximum Likelihood (FIML) method. Growth Mixture Model was used to analyse growth patterns of children from birth until 36 months. Results: On average, Pakistani children were 190 g lighter than white British children at birth. Based on our Growth Mixture Model results, the study children had three distinct growth patterns: 'normal growers' (95.9%), 'fast growers' (2.5%) and 'slow growers' (1.6%). The Pakistani children were more likely to be in either the 'fast' (OR=2.90; 95% CI 0.91 to 9.25) or 'slow' (OR=15.63; 95% CI 1.06 to 230) grower class than the white British. Pakistani children showed faster growth than the white British between 3 and 36 months of age. Conclusions: In this growth study we have identified that the study children have three distinct growth patterns. These growth patterns may provide greater insight in predicting the risk of childhood or early adulthood diseases in life-course studies.